THE ROLE OF PRIMARY SCHOOL TEACHERS IN INCREASING EFFICIENCY OF LESSONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides detailed information on the importance of personal qualities and pedagogical skills of the teacher in improving the effectiveness of primary education, as well as the ability of the teacher to shape the learning process using pedagogical and psychological tools.